Penerapan Blockchain untuk Verifikasi Sertifikat Akademik di Pendidikan Tinggi: Tinjauan Sistematis - Julian Lirama Junior Pandari; Krismiyati; Theophilus Wellem (Institut Teknologi Garut, 2026)
Digital transformation in higher education requires secure and efficient academic certificate verification to address the limitations of conventional systems, such as the risk of forgery and slow processing. Blockchain technology offers a transparent distributed data recording solution; however, its implementation in developing countries still faces challenges related to infrastructure and regulation. This study uses the Systematic Literature Review (SLR) method guided by PRISMA. Literature searches were conducted in Scopus, IEEE Xplore, Google Scholar, ACM Digital Library, and SpringerLink databases to explore publications from 2017 to 2024. From all identified articles, 35 studies were selected through a screening and quality assessment process, then analyzed narratively and synthesized using a thematic approach. This study produces a comprehensive synthesis of the evolution of blockchain implementation in academic certificate verification and identifies a blockchain model that integrates Hyperledger Fabric, Verifiable Credentials, and the InterPlanetary File System as a hybrid architectural approach. The proposed model is not viewed as a replacement for existing national systems, but rather as an additional trust layer that complements them. This approach is considered capable of balancing data security, scalability, and resource efficiency in developing countries, while also identifying research gaps for further empirical validation. The limitation of this study lies in its literature review nature, meaning that its findings remain conceptual.